PENGILMUAN ISLAM ZIAUDDIN SARDAR DAN RELEVANSINYA BAGI PERGURUAN TINGGI KEAGAMAAN ISLAM DI INDONESIA - Farkhan Fuady; Raha Bistara (UIN Raden Mas Said Surakarta, 2022)
This article wants to explain how the development of science. Especially those related to Islam and Science. Every civilization makes efforts to continuously develop their knowledge (Religion and Science). Western and Eastern civilizations, especially Islam, which continue to compete to catch up with the West feel this dilemma. For this reason, it is necessary to have a Transfer of Knowledge process or even a cross between two scientific poles. Sardar is present as a Muslim thinker who wants to reconcile the two with the idea of ​​​​Islamic Science. this idea as self-criticism and offer in Islamic epistemology. Self-criticism in the sense of Islamic scholarship is present as a critique of the idea of ​​Islamization of Science initiated by al-Faruqi and the offer of Islamic epistemology as a new idea to bring together Islam and Science. This offer is a new scientific alternative for the Muslim generation who were born in the modern century, especially for PTKIN which will change its status from IAIN to UIN. Sardar plants are considered relevant to the new UIN in finding their knowledge which does not have two different poles, namely Islam and Science. By using Sardar's idea, the new UIN has a distinctive scientific style that other Islamic institutions do not have.